Evaluation of the current MicroRNAs expression levels as potential biomarkers in Oral Squamous Cell Carcinoma: Evaluation of the current MicroRNAs in OSCC - Tahmasebi, Elahe; Kaboudanian Ardestani, Ali; Madihi, Negar; Abbasiparashkouh, Zahra; Abbasi Maleki, Sanam; Yazdanian, Mohsen; Khafaei, Mostafa; Movafagh, Abolfazl; Tavallaie, Mahmood (Cellular and Molecular Biology, 2022)
As the most common malignancy, oral squamous cell carcinoma (OSCC) is typically fatal. The survival of patients with oral cancer has not improved, and tumor recurrence remains high. During tumorigenesis, microRNAs (miRNAs) regulate gene expression. Patients’ life expectancy can be determined by prognostic survival biomarkers, which can focus therapy on specific targets. This study evaluated five miRNAs associated with OSCC for their prognostic impact. It was determined through microarray analysis and quantitative reverse transcription polymerase chain reaction that there was a significant difference in the expression of miRNAs between OSCC patients and control patients in plasma. We used the unpaired t-tests and the Mann-Whitney test to conduct the statistical analysis. Based on the study’s results, five miRNAs have been found to have significantly different expression levels in the plasma of patients with OSCC; in particular, miR-31 was found to have a significantly higher expression level in OSCC patients’ plasma as compared with healthy controls. Aside from that, there was a significant reduction in the expression of miR-100, miR-199a, miR-203, and mir345 in the plasma of OSCC patients (P < 0.05). To better understand the importance of miRNAs in OSCC, various OSCC cases were analyzed. Detecting miRNAs in plasma may be a useful diagnostic tool for oral squamous cell carcinoma.